2011
DOI: 10.1086/659401
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic (H1N1) 2009 Influenza in Hospitalized Children in Manitoba: Nosocomial Transmission and Lessons Learned from the First Wave

Abstract: Infection with pandemic (H1N1) 2009 influenza virus resulted in a substantial number of hospitalizations of pediatric patients in Manitoba, including those with nosocomial cases, thereby stressing the capacity of WCH. Immediate therapy with oseltamivir on admission to the hospital resulted in a significantly reduced length of hospitalization. This, coupled with intensified infection prevention and control practices, halted nosocomial transmission. These strategies should be considered in future pandemic influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 5 publications
0
21
0
2
Order By: Relevance
“…Enstone et al reported that 93% of UK children with nosocomial pH1N1 had serious underlying illnesses, while Fanella et al from Canada reported that all nosocomial cases had underlying medical conditions. 13,14 Both host and environmental factors could be responsible. Generalized immunosuppression, poor functioning of a specific organ/system (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enstone et al reported that 93% of UK children with nosocomial pH1N1 had serious underlying illnesses, while Fanella et al from Canada reported that all nosocomial cases had underlying medical conditions. 13,14 Both host and environmental factors could be responsible. Generalized immunosuppression, poor functioning of a specific organ/system (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear if prompt antiviral therapy decreased the severity of illnesses in children with nosocomial influenza, but antiviral drug usage in this cohort was comparable with published data. 13,14 A limitation of this study is that contact tracing was not performed actively. Only five of 42 (12%) patients with nosocomial pH1N1 whose data were available knew of a contact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Several studies from around the world have included children and adults admitted to hospital or intensive care units with pH1N1 infection. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] However, these data vary in format and emphasis, making direct comparison between studies difficult. Furthermore, data on severe outcomes (including death) and risk factors for severe outcomes are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Visitors of visitors for acute illness has been efficacious in reducing the spread of influenza [7] and norovirus [8]. During the severe acute respiratory syndrome (SARS) epidemic, all hospital visitors were screened at hospital entry for acute illness using questionnaires and temperature assessment [9].…”
Section: General Infection Prevention Strategies and Healthcare Visitorsmentioning
confidence: 99%